Analisis terkait Minat Belajar Peserta Didik dalam Pembelajaran IPAS Berbasis Buku Cetak di Sekolah Dasar - Dina Ramadhani; Fadila Khairumi; Adrias Adrias; Salmaini Safitri Syam (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to determine the impact of the use of textbooks on the learning interests of grade IV students of SDN 01 Gunung Tuleh in the subject of Natural and Social Sciences (IPAS). This study uses a qualitative method with data collection techniques through observation and interviews. The results of the study indicate that most students are less interested in learning IPAS whose main learning sources come from printed books. Several factors that cause low student learning interest include the lack of variation in teaching methods used by teachers and the lack of relevance of the material to students' daily lives. Based on these findings, it is recommended that teachers use more varied, interactive, and innovative teaching materials, as well as materials related to students' daily experiences to increase their involvement and motivation in learning IPAS. With a more interesting and relevant approach, it is hoped that students' interest in learning IPAS can increase significantly.